Evaluasi Implementasi Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19 Di Madrasah Aliyah Labolatorium Kota Jambi - Gemilang, Muhammad Insan; Munandar, Aris (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research aims to evaluate the implementation of distance learning during the Covid-19 pandemic. During the Covid-19 period, learning was carried out online (distance learning) using several applications such as WhatsApp, class room, Telegram, Zoom, and so on. Online learning causes learning not to run optimally so that it does not achieve the learning goals of teachers. This research used a direct interview method with the deputy head of curriculum at the school. The results of this research can be concluded that online learning makes teaching and learning activities not optimal, as well as a lack of teacher supervision of student activities during learning, because many students find it difficult during online learning, for example, poor network, insufficient memory storage, so you cannot download applications to support online learning activities.